Hedonic analysis of yearling bull prices for a land grant university: determining the value of a pulmonary arterial pressure (PAP) score - Kessler, Beth A., author; Frasier, Marshall, advisor; Pendell, Dustin, advisor; Enns, R. Mark, committee member (Colorado State University. Libraries, 2013)
Producers look for various traits in seedstock bulls to enhance their herds and will often pay a premium for those traits. One particular physical trait which is of interest to producers in the mountainous western United States is for cattle that can thrive at a high altitude. Cattle in this environment can be prone to developing High Altitude Disease (HAD) which has been shown to cause weakness, lethargy, and death. Pulmonary Arterial Pressure (PAP) is a test used to detect the likelihood of an animal of developing HAD. The test provides a score from 30 to 130 with scores over 45 indicating an animal is more likely to develop the disease. Colorado State University specializes in cattle genetics; and in particular, manages a herd that has low PAP scores, strong early growth, fertility, and maternal ability. The center holds an annual auction to sell their yearling bulls each spring. Data was collected from three years of sales (2011, 2012, and 2013), and hedonic models were estimated using ordinary least squares (OLS) to determine the value of simple performance measurements (SPM), expected progeny differences (EPD), and marketing factors of the yearling bulls sold at these auctions. In one model, a continuous variable for PAP score was found to be significant and have a negative relationship with sale price. In a second model, a dummy variable for a PAP score under 46 was shown to be significant and have a positive relationship with sale price. In a third model using standardized continuous variables, PAP score was shown to have the most influence on sales price, followed by EPD for yearling weight, frame score, and EPD for stayability. The results suggest that producers are willing to pay a premium for a low PAP score.
Keywords: hedonic model; yearling bull prices; pulmonary arterial pressure; PAP